H2-rich syngas production from air gasification of date palm waste: an experimental and modeling investigation - Kabli, M.R. (Springer Science and Business Media Deutschland GmbH, 2022)
The energy generation from renewable sources is in prime focus not only oil-importing countries as well as oil-exporting countries. This study aims to probe the energy generation (syngas) from Saudi Arabian date palm fronds through air gasification in a downdraft fixed-bed system. In addition, an equilibrium process simulation model was developed using Aspen Plus, and predicted results were compared with experimental results. Furthermore, the mass and energy flows of the system were also analyzed. In parametric study, the impact of temperature (600â900Â Â°C), particle size (2â6Â mm), and air flowrate (1â4Â l/min) were investigatedÂ on syngas composition and gasification performance parameters higher heating value, gas yield, carbon conversion efficiency, and cold gas efficiency. The results indicate that H2 concentration was enhanced with the rise of temperature and particle size from 12.12 to 26 vol. and 26.02 to 26.89 vol. respectively. The enrichment of H2 concentration was due to the activation of endothermic reaction and methane-reforming reaction as CH4 was dropped up to 12.6 vol with increased temperature. The higher heating valueÂ of syngas, carbon conversion efficiency, and cold gas efficiency have shown an increasing profile with increased temperature and air flowrate. The gas concentration profile obtained from the simulation model found good agreement with the experimental results. The energy analysis shows that the process is highly energy consuming, and most of the energy waste is in the form of condensate that could be potentially utilized. This study will be helpful for researchers and commercial enterprises to produce syngas from Saudi Arabian date palm fronds. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.